Modelo de asignación de compras a proveedores considerando su flexibilidad y probabilidad de incumplimiento en la entrega (2012)
Supplier selection is a critical process in supply chain management and business competitiveness. This article presents a decision-making model that optimizes allocation of demand across a set of suppliers considering expected losses associated with delivery defaults, purchasing costs, unforeseen costs of non-delivered supplies, and supplier management costs. An experimental and sensitivity analysis was carried out to study the behavior of the model with regard to key parameters. The results reveal that the proposed model is sensitive to these parameters and demonstrate the usefulness of the model to decision makers in this field.